L2 Selves Motivation Among Thai Students: A Case study in Sciences, and Humanities and Social Sciences Students at a Government University - Worragittanont , Natanon (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
Learning the English language has become ever more important with the increasing adoption of English as the global language. Students from Thailand should be able to communicate with people from around the world and enhance their employment prospects by being able to speak English. Many researchers have investigated the low levels of competence in English amongst students in Thailand, looking for a cause. One potential cause is low motivation. A five point Likert scale questionnaire and semi-structured interviews were employed for collecting data from 385 participants. Participants were split into two categories, those studying science subjects (125 respondents) and those studying the humanities and social sciences (260). This research demonstrated that there was no difference between students in sciences and those in humanities and social sciences in terms of learning achievement, strategies for learning languages, L2 selves, or contextual factors. Additionally, all the factors seem to have a significant relationship with each other, meaning that when one has significance, the others will also. Qualitative data demonstrated that students who achieve well in English are in the habit of regularly practicing their English skills, both in the classroom and elsewhere; students who do not achieve so well regard English as simply an academic subject and have no desire to practice outside the classroom, although they do accept English when it is involved in entertainment.